Thromboprophylaxis with enoxaparin in Germany - Kröger, K.; Paar, W. D. (Phlebologie, 2006)
Aim, methods: Two independent post-marketing surveys were performed in 2001 and 2002/03. Results: Patient demographic data and co-medication use were similar between surveys. The most common acute medical illnesses were heart failure and acute respiratory failure. The most common venous thromboembolism (VTE) risk factors were age >65 years, varicose veins and obesity. Physicians estimated the VTE risk as moderate in 25-29%, high in 53-56% and very high in 18-20% of patients. Thromboprophylaxis with enoxaparin was given to patients for approximately 20-25 days. Clinical symptoms for VTE were recorded in 0.9% of patients during thromboprophylaxis. No bleeding episodes were observed. The general adverse reaction profile with enoxaparin was good and adverse events occurred in less than 2.5% of patients. Of these adverse events, 0.2% were allergic reactions thought to be associated with enoxaparin. Conclusion: Thromboprophylaxis with enoxaparin was safe in this ‘real-world’ population. Moreover, patient compliance, tolerability, and acceptance were high.
Keywords: Venous thromboembolism; thromboprophylaxis; medical outpatients; acute medical illness